1981
DOI: 10.1084/jem.153.3.520
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell-mediated tumor-cell cytotoxicity. Role of the peroxidase system.

Abstract: Mast cells have been demonstrated in increased numbers in certain neoplasms in humans (1-3) and in both spontaneous tumors and those induced by carcinogenic agents in animals (4, 5). Eosinophils are often closely associated with mast cells in inflammatory reactions, and these cells also are present in increased numbers in some neoplasms (6). The role of these inflammatory cells in the host defense against tumors is unknown.A number of distinct peroxidases exist in mammalian tissues which differ in primary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
46
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 17 publications
6
46
0
1
Order By: Relevance
“…That eosinophils may, however, also potentiate basophil and mast cell functions is shown by findings that relatively low concentrations of eosinophil peroxidase in the presence of hydrogen peroxide and a halide induce noncytotoxic degranulation of rat peritoneal mast cells (37) and also enhance mast cell tumoricidal activity (38). The results presented here extend possible activation by eosinophils to include the effect of MBP on human basophils and also rat mast cells.…”
Section: Discussionsupporting
confidence: 48%
“…That eosinophils may, however, also potentiate basophil and mast cell functions is shown by findings that relatively low concentrations of eosinophil peroxidase in the presence of hydrogen peroxide and a halide induce noncytotoxic degranulation of rat peritoneal mast cells (37) and also enhance mast cell tumoricidal activity (38). The results presented here extend possible activation by eosinophils to include the effect of MBP on human basophils and also rat mast cells.…”
Section: Discussionsupporting
confidence: 48%
“…It has been reported that the incidence of metastases as well as the appearance of tumours correlates inversely with tissue histamine level and mast cell count (Burtin et al, 1985). Interestingly, isolated mast cells were shown to inactivate tumour cells selectively in vitro (Henderson et al, 1981). These findings suggest that mast cells may play a role in inhibiting tumour metastases and suppressing growth of primary tumours.…”
Section: Discussionmentioning
confidence: 93%
“…The role of mast cells in tumour growth has been studied extensively in experimental tumours (Fisher and Fisher, 1965;Tanooka et al, 1982;Burtin et al, 1985), however, the significance of mast cell infiltration around human tumours has not been well studied, even though accumulation of mast cells around tumours was first reported a decade ago (Dimitriadou and Koutsilieris, 1997). Most studies have shown that mast cells prevent tumour growth (Farram and Nelson, 1980;Henderson et al, 1981;Ghiara et al, 1985;Benyon et al, 1991). In contrast, in a heterocyclic amine-induced rat PCa model, Nakai et al (2007) reported increased infiltration of stromal mast cell in the ventral prostate, with increased prostatic epithelial proliferation, suggesting that mast cells may have beneficial roles in progression of PCa (Nakai et al, 2007).…”
mentioning
confidence: 99%
“…On the other hand, mast cell granules released during inflammation may contribute to the tissue irritation caused by other eosinophil proteins. It has been suggested that mast cells, which normally contain a small amount of granular peroxidase activity [244], may internalize exogenous EPO using a vesicular transport system and incorporate the peroxidase in their cytoplasmic granules [243,246,247].…”
Section: Mast Cells and Basophilsmentioning
confidence: 99%
“…It has been shown that EPO binds to the negativelycharged mast cell granule to form a complex that retains toxic activity to bacteria [242] and tumour cells [243] when supplemented with H 2 O 2 and a halide [242,244]. Since EPO at high H 2 O 2 concentrations and the EPO/H 2 O 2 / halide complex at lower H 2 O 2 concentrations can initiate mast cell granule release [245], it is conceivable that mast cells and eosinophils may act synergistically to improve host defence.…”
Section: Mast Cells and Basophilsmentioning
confidence: 99%